Bacteremia in Hemodialysis Patients With Hepatitis C. (March 2015) - Chebrolu, Puja; Colombo, Rhonda E.; Baer, Stephanie; Gallaher, T. Ryan; Atwater, Sara; Kheda, Mufaddal; Nahman, N. Stanley; Kintziger, Kristina W.
Abstract: Background: Hepatitis C virus (HCV) infection and bacteremia are common comorbidities in hemodialysis patients. A specific relationship between HCV infection and bacteremia has not been defined; however, there is evidence of immune compromise in both HCV-infected and uremic patients, suggesting that this group may be at higher risk for infection. Methods: We investigated risk factors and mortality associated with bacteremia in HCV-infected hemodialysis patients from the United States Renal Data System. Results: During the 4-year study period, HCV was present in 2.1% of 355, 084 patients initiating hemodialysis. When compared with the total population, the rate of bacteremia was significantly higher in patients with HCV (38.3% versus 21.8%). The adjusted relative risk (RR) for bacteremia was higher in HCV versus all patients (relative risk, 95% confidence interval [CI]) in the presence of methicillin-resistant Staphylococcus aureus infection (2.64, CI: 2.58–2.70 versus 2.32, CI: 2.27–2.38), HIV (1.93, CI: 1.85–2.02 versus 1.86, CI: 1.77–1.95) urinary tract infection (1.79, CI: 1.77, 1.82 versus 1.64, CI: 1.61–1.67) and cirrhosis (1.49, CI: 1.45–1.54 versus 1.29, CI: 1.25–1.34). The hazard ratio (95% CI) for death was higher in HCV versus all patients at 1.69 (CI: 1.58–1.81) versus 1.54 (CI: 1.53–1.56). Conclusions: These data indicate that several clinical covariates increase the risk of bacteremia in hemodialysis patients, with the magnitude of that risk being further increased by HCV infection. Improving outcomes in HCV-infected hemodialysis patients will likely be dependent on aggressive diagnosis and treatment of both HCV and bacteremia. Abstract : Supplemental Digital Content is Available in the Text.